La acumulación de basuras como material geotécnico I: fundamentos técnicos - Espinosa Silva, Augusto; González García, Alvaro J. (Revista de Ingeniería, 2001)
Human wastes constitute an evergrowing by-product of civilization. Several catastrophic landslides have taken place in these so-called sanitary land fills. It is apparent that geotechnical and environmental engineers follow divergent paths to solve the related technical problems. Part I of this paper addresses the development of mechanical sciences leading to Soil Mechanics (1925) and Rock Mechanics (1960). Part II is dedicated to show how these sciences and arts or geomechanics are applied to huge accumulations of garbage of what could be referred to as anthropic waste deposits.